Assessment of Levels of premenstrual psychological and physical Problems (Premenstrual Syndrome-PMS) of Students of the Colleges of Bab Al-Mua’dham Complex/ University of Baghdad - ibrahim, maan; hasan, rajaa; fadhil, sarab (Iraqi National Journal of Nursing Specialties, 2017)
Objectives: To assess levels of premenstrual psychological disorders of the students in Bab Al-Mua’dham Complex and to find out the relationship between the levels of premenstrual psychological and physical disorders and some demographic characteristics of the students. Methodology: A descriptive study was accomplished throughout the period from the 1st of October, 2015 to the 8th of July, 2016 to assess the psychological and physical problems. A purposive sample of 313 students distributed among different colleges of Bab Al-Mua’dam complex distributed as following: 82 students are from college of Arts; 79 students are from College of Languages; 48 students are from college of Islamic Sciences: and 104 are from College of Nursing. For the purposes of the study a questionnaire was constructed which represents the premenstrual symptoms screening tool (PSST) by Steiner et al.(2003)(1). This questionnaire consists of three parts: first, the demographic characteristics of students agreed to participate in the present study; Second part contains 16 items represents the psychological problems and the third part is supposed to measure the physical problems and contains 11 items. Levels of severity of problems were determined by using the quartiles step. The data of the study were analysed by applying descriptive data analysis: frequencies, percentages and tables of distribution; and inferential data analysis: Pearson coefficient correlation and Chi square, using the statistical analysis program of SPSS 19th version. Results: The present study reveals that more than half of the students are 20 and 21 years old; the majority of them are unmarried; one third of the sample are from the first class; more than three quarters have different levels of severity of psychological and physical problems distributed among slight level to the levels which interrupt the daily activities and/ or change the life style. The study has not found any differences between married and unmarried students. Also, the study does not find significant association between demographic characteristics and psychological problems but there is a significant relationship between the study stage and physical problems and age and psycho-physical problems. Recommendations: The present study recommends that medical and health follow up for students with levels which interrupt the daily activities and/ or change the life style of those students. Further studies concerning the impact of psychological and physical problems upon the academic achievement and also upon social relationship and the way the student deals with her family and society. Further studies aimed to discover the mood fluctuations which might result to suicidal ideation.